DOCK2 protects against bacterial sepsis by constraining T helper 1 response - Ye, Shusen; Huang, Linzi; Zheng, Yuhao; Liu, Shanshan; Wang, Xiangyang; Yu, Haoyuan; Zhu, Lisi; Liang, Texi; Wang, Yifei; Zhang, Chunmin; Wu, Fan; Ye, Lilin; et al. (Frontiers in Immunology, 2025)
BackgroundSepsis is a systemic host response to infection with life-threatening consequence which ranks among the top ten causes of death worldwide. Nevertheless, our understanding of the molecular and cellular impact of sepsis remains rudimentary.MethodsA mouse sepsis model was established through LPS induction and Escherichia coli (E. coli) infection. Flow cytometry and enzyme-linked immunosorbent assay (ELISA) were used to detect T helper 1 (Th1) cell subsets and serum pro-inflammatory cytokines in septic mice. Additionally, in vivo neutralization experiments were conducted to block IFN-γ and CD4+ T cells, respectively, to explore the regulatory effect of DOCK2 on septic mice. Finally, the regulatory mechanism of DOCK2 was analyzed using an in vivo RNA-seq system.ResultsWe identified dedicator of cytokinesis 2 (DOCK2) is a critical downregulating factor for LPS signal pathways. DOCK2-deficient mice were highly sensitive to LPS-induced sepsis and E. coli sepsis with increased levels of inflammatory cytokines, especially IFN-γ which were mainly due to hyperresponsive Th1 cells. Ulteriorly, we verified the vital role of DOCK2-mediated Th1 cells in sepsis by neutralizing both IFN-γ and CD4 and found both of which blockade reduced the severity of sepsis in Dock2−/− mice. Mechanically, DOCK2-mediated cell cycle progression and cytokine signaling act in concert to govern peripheral Th1 cell fate.ConclusionOur data indicates that DOCK2 acts as a protective role in regulating systemic inflammation and multi-organ injury in bacterial sepsis by constraining Th1 response. These findings provide new targets for immunomodulatory therapy of sepsis, suggesting that targeting the DOCK2-Th1 axis may become a new strategy to improve systemic inflammatory responses associated with bacterial infections.